Evaluation and comparison of the effectiveness and safety of diferente facial rejuvenation techniques (Research, Society and Development, 2023)
The study reviewed the most common techniques in dentistry, including threads for facial lifting, injectable platelet-     rich fibrin (I-PRF), hyaluronic acid, botulinum toxin and microneedling. The objective of this research was to present and compare the main facial rejuvenation techniques on the market. The methodology used in this study was qualitative in nature, with the elaboration of a bibliographic narrative review in the LILACSM SciELO and MEDLINE databases relevant to the proposed topic. To evaluate efficacy, parameters such as wrinkle reduction and improvement in skin texture were considered, while safety was assessed based on side effects and recovery time. The results showed that all techniques were effective in facial rejuvenation, but the results varied according to the technique used and the patients' needs. Overall, the study concluded that the choice of facial rejuvenation technique should be based on the individual needs of the patient and the skills and experience of the professional performing the procedure.